Anthem - Wiles, Deborah (Wiles, Deborah. Sixties trilogy, 2019)
Fourteen-year-old Molly and her seventeen-year-old cousin, Norman, are told to travel from Charleston to San Francisco to find Molly's older brother and return him home as he's been drafted for the war in Vietnam. The teens reluctantly set out in an old school bus, and along their journey, they discover the real face of America in a tumultuous time. Includes montages of actual news photos, quotes, headlines, and lyrics throughout.